Inhibition of DOT1L by Half-Selenopsammaplin A Analogs Suppresses Tumor Growth and EMT-Mediated Metastasis in Triple-Negative Breast Cancer - Woong Sub Byun; Gyu Ho Lee; Hyeung-geun Park; Sang Kook Lee (MDPI AG, 2020)
Due to a lack of hormone receptors, current treatment strategies for triple-negative breast cancer (TNBC) are limited with frequent disease recurrence and metastasis. Recent findings have suggested that aberrant methylation of histone H3 lysine 79 residue (H3K79me) by the histone methyltransferase disruptor of telomeric silencing 1-like (DOT1L) is a potential therapeutic target for TNBC clinical management. Therefore, we developed DOT1L inhibitors as potential antitumor agents against TNBC cells. We reveal that a synthetic half-selenopsammaplin A analog 9l (subsequently known as 9l) exhibited inhibitory activity against DOT1L-mediated H3K79 methylation, and showed antitumor activity in TNBC cells. The analog 9l also significantly inhibited TNBC invasion and migration via the modulation of epithelial-mesenchymal transition (EMT) markers, including N-cadherin and vimentin downregulation and E-cadherin upregulation. In an MDA-MB-231/Luc-implanted orthotopic mouse metastasis model, treatment with 9l effectively inhibited tumor growth and lung metastasis via DOT1L regulatory activity and EMT processes. Taken together, these findings highlight the potential of 9l as a novel therapeutic candidate for treating metastatic TNBC via DOT1L modulation.